Modélisation SIG de l’accessibilité par co-modalité en favorisant l’usage des transports en commun en Wallonie et Fédération Wallonie-Bruxelles - Alexandre Leclercq; Martin Grandjean; Yves Hanin (Cybergeo, 2015)
The accessibility of territories is at the heart of concerns in terms of attractiveness and sustainability (greenhouse gas emissions, etc.). And it therefore plays a key role in strategies of territory structuration. A spatial model has been developed to study the accessibility by co-modality promoting public transport in Wallonia. This Decision Support System is part of a methodological process to develop and consolidate spatial databases using the full range of information available on the Web (traveltime, transfert time) and the analytical power of a geographic information system.